Pewarisan Nilai-Nilai Tradisi Budaya Suku Anak Dalam Air Hitam, Sarolangun, Provinsi Jambi - Priazki Hajri; Junaidi Indrawadi (Universitas Negeri Medan, 2021)
This article aims to describe how the inheritance of the cultural traditions values of the Suku Anak Dalam Air Hitam, Sarolangun, Jambi. The research was conducted with a qualitative approach. Data collected through observation, interviews, documentation. Data were analyzed using data analysis techniques, namely data reduction, data presentation, and drawing conclusions. Testing the validity of the data by triangulation of sources. The results of the study found that the inheritance of cultural traditions values Suku Anak Dalam Air Hitam, Sarongun Jambi was carried out face-to-face, the involvement of the younger generation (children) in culture, and customary rules. The values inherited are individual, social and love values for the country.